Interculturalism facing real problems. Educational research, otherness, conceptions and skin colour - Luca Agostinetto; Lisa Bugno; Gaia Moretto (University of Bologna, 2023)
This paper stands in line with educational research on children's conception of otherness through skin colour. The first part focuses on the epistemological context: it can be referred to the complexity paradigm and to a pragmatic approach of investigation, both aimed at confronting real problems such as the connection between colourism and racism. After considering some of the main research directions in this field, the second part articulates the construct of  conception as the basis of the research framework. Finally, the third part describes the research design, the steps that led to the text stimulus outline, and what is in progress, looking for a constructive dialogue with other active processes in the national scientific community.